Crystal structure of the (REE)-uranyl carbonate mineral shabaite-(Nd) - Plasil,J.; Skoda,R. (Journal of Geosciences, 2017)
Shabaite-(Nd) is a rare supergene mineral formed during alteration-hydration weathering of uraninite; its structure has remained unknown until now. Based on single-crystal X-ray diffraction data, shabaite-(Nd) is triclinic, twinned (leading to a pseudo-monoclinic diffraction pattern), space group P-1, with a = 8.3835(5), b = 9.2766(12), c = 31.7519(3) Å, α = 90.058(3), β = 89.945(4), γ = 90.331(4)°, V = 2469.3(4) Å3 and Z = 4. The structure was refined from diffraction data to R = 0.060 for 8434 unique observed reflections. The structure of shabaite-(Nd) is based upon finite clusters of polyhedra, the well-known uranyl-tricarbonate cluster (referred to as UTC), the Ca-polyhedra linked to UTC and infinite sheets of Nd-polyhedra with internal Nd-O-C linkages. The infinite sheets of Nd-polyhedra are stacked perpendicular to c; to the UTC are staggered approximately perpendicular to the Nd-based sheets (thus approx. parallel to c), forming electroneutral ({Nd3+2(CO3)2-2(H2O)2}2+{Ca(H2O)5}2+[(UO2)(CO3)3]4-)0 layers. Adjacent layers are linked by hydrogen bonds. The ratio of elements in the chemical formula of shabaite-(Nd), obtained from the structure refinement, Nd2Ca[(UO2)(CO3)3](CO3)2(H2O)10.5, Z = 4, was confirmed by an electron-microprobe study. The resulting empirical formula for the average of six point analyses is Ca1.01(Nd0.64Ce0.32Sm0.28Gd0.19Y0.19Pr0.13Dy0.10La0.07Tb0.05Ho0.01)Σ1.98(UO2)(CO3)4.98(H2O)10.5 (based on 1 U apfu). A discussion of the crystal-structural relationships of shabaite-(Nd) and chemically related minerals is given as well as discussion of complexities of their crystal structures.
Keywords: shabaite-(Nd); uranyl carbonate; rare-earth elements; crystal structure; mineral evolution